Percutaneous Transcatheter Embolization of Pulmonary Artery Pseudoaneurysms Causing Massive Hemoptysis: Two Different Case Scenarios. (February 2014) - Saddekni, Souheil; Aal, Ahmed Kamel Abdel; Gaddikeri, Santhosh; Hadi, Samir; Singh, Satinder P.
Systemic bronchial arterial circulation is the most common source for massive hemoptysis. Rarely, the source of bleeding can be the pulmonary artery. We report 2 different case scenarios of massive hemoptysis due to different etiologies, in which the source of bleeding was the pulmonary artery. Both the patients were treated with percutaneous transcatheter embolotherapy using coils. The 2 cases highlight the importance of considering pulmonary arterial etiology as the cause of hemoptysis while reporting diagnostic computed tomography studies and tailoring the interventional technique toward performing pulmonary angiography instead of searching for a systemic arterial source for hemoptysis.